Endoscopic vacuum therapy in the upper gastrointestinal tract - Boonstra, Kirsten; Pattynama, Lisanne M. D.; van Herwaarden, Yasmijn J.; Eshuis, Wietse J.; Pouw, Roos E. (Frontiers in Gastroenterology, 2025)
Endoscopic vacuum therapy (EVT) is a promising and versatile intervention for managing transmural defects in the upper gastrointestinal tract. Despite challenges, EVT exhibits great efficacy and safety, emphasizing the need for standardized protocols and evidence-based practices. We provide an overview, including mechanism, indications, types of EVT devices and complications, guiding clinicians in decision-making. Common challenges in EVT are highlighted, facilitating adequate implementation of EVT and helping to avoid common mistakes in daily practice.